Studies on CD36 deficiency in South China: Two cases demonstrating the clinical impact of anti-CD36 antibodies - Xu, Xiuzhang; Ye, Xin; Xia, Wenjie; Liu, Jing; Ding, Haoqiang; Deng, Jing; Chen, Yangkai; Shao, Yuan; Wang, Jiali; Fu, Yongshui; Santoso, Sentot (Thrombosis and Haemostasis, 2013)
CD36 (also known as GPIV) deficiency is known to be responsible for the production of anti-Naka antibodies in different clinical settings such as fetal/neonatal alloimmune thrombocytopenia (FNAIT), platelet transfusion refractoriness (PTR) and post-transfusion purpura (PTP). However, no data regarding the relevance of CD36 immunisation is currently available for China. In this study, healthy blood donors were typed for CD36 deficiency using flow cytometry. Nucleotide sequencing was performed to identify the molecular basis underlying the CD36 deficiency. Anti-Naka antibodies in CD36-deficient individuals were analysed by ELISA and flow cytometry. By analysis of 998 healthy blood donors, 18 individuals failed to express CD36 on their platelets. In 5/12 individuals no CD36 expression was detected both on platelets and monocytes. This result suggested that the frequencies of type I CD36 deficiency (platelets and monocytes) and type II CD36 deficiency (platelets only) are approximately 0.5 and 1.3%, respectively. Nucleotide sequencing analysis of type I CD36 deficient individuals revealed eight different mutations; four of them were not described so far. However, 1228–1239de/ ATTGTGCCTATT and 329–330de/AC appear to be the most common mutations related to type I CD36 deficiency in South Chinese population. Further analysis showed that 1/5 type I CD36 deficient individuals developed anti-Naka antibodies. In addition, anti-Naka antibodies could be identified in two cases of thrombocytopenia associated with FNAIT and PTR. In conclusion, more than 0.5% of CD36 type I-deficient individuals are at risk to be immunised through blood transfusion or pregnancy in China. Testing of anti-Naka antibodies should be considered in FNAIT and PTR suspected cases. A registry of CD36-deficient donors should be established to allow treatment of immune-mediated bleeding disorders caused by anti-Naka antibodies.
Keywords: CD36; platelet glycoprotein IV; anti-Naka; gene mutation; neonatal alloimmune thrombocytopenia; platelet transfusion refractoriness